Modifications and Applications of Metal-Organic-Framework-Based Materials for Photocatalysis - Weimin Ma; Liang Yu; Pei Kang; Zhiyun Chu; Yingxuan Li (Molecules)
Metal–organic frameworks (MOFs) represent a category of crystalline materials formed by the combination of metal ions or clusters with organic linkers, which have emerged as a prominent research focus in the field of photocatalysis. Owing to their distinctive characteristics, including structural diversity and configurations, significant porosity, and an extensive specific surface area, they provide a flexible foundation for various potential applications in photocatalysis. In recent years, researchers have tackled many issues in the MOF-based photocatalytic yield. However, limited light adsorption regions, lack of active sites and active species, and insufficient efficiency of photogenerated charge carrier separation substantially hinder the photocatalytic performance. In this review, we summarized the strategies to improve the photocatalytic performance and recent developments achieved in MOF and MOF-based photocatalysis, including water splitting, CO2 conversion, photocatalytic degradation of pollutants, and photocatalytic nitrogen fixation into ammonia. In conclusion, the existing challenges and prospective advancements in MOF-based photocatalysis are also discussed.